2023
DOI: 10.5137/1019-5149.jtn.44241-23.1
|View full text |Cite
|
Sign up to set email alerts
|

Common vertebral fracture level after the 2023 turkey earthquake, thoracolumbar junction, due to hyper-flexed and fixed posture at trýangle of life areas

Abstract: AIM:To assess the frequency of thoracolumbar junction (TLJ) fractures (T10-L2) in survivors of the 2023 East Turkey earthquake. MATERIAL and METHODS:This single-center retrospective stdy evaluated 10 earthquake survivors, who were trapped under the rubble and rescued alive by rescue teams, and were assessed for spinal trauma after the earthquake in Eastern Turkey on February 6, 2023. All patients underwent full spinal magnetic resonance imaging and computed tomography examinations to determine the level of spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…T2-weighted MRI sequences are particularly useful for identifying hematoma, whereas STIR images facilitate the detection of spine fractures, edema, and spinal ligament injuries. [8] In this study, we opted for CT scans to visualize fractures more effectively, while MRI was preferred for identifying spinal cord injuries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…T2-weighted MRI sequences are particularly useful for identifying hematoma, whereas STIR images facilitate the detection of spine fractures, edema, and spinal ligament injuries. [8] In this study, we opted for CT scans to visualize fractures more effectively, while MRI was preferred for identifying spinal cord injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently across studies, the thoracolumbar region, particularly the thoracolumbar junction, is identified as the most commonly affected spinal segment in earthquake-related injuries, a finding that aligns with our study. [3,4,8,[13][14][15][16][17][18] Various studies have sought to understand why the thoracolumbar region is so frequently affected in spinal fractures resulting from earthquakes. Alpergin et al [8] suggested that the high incidence of thoracolumbar junction involvement is due to the tendency of individuals to adopt a hyperflexed posture during an earthquake, seeking to protect themselves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations